KEBIJAKAN MORATORIUM REMISI DAN PEMBEBASAN BERSYARAT BAGI NARAPIDANA TINDAK PIDANA KORUPSI DI INDONESIA - Yonna Beatrix Salamor (SASI, 2016)
Effect of eradication of corruption in Indonesia and according to Law Number 31 Year 1999jo. Law No. 20 of 2001 on Corruption Eradication, explaining that the corruption that hasbeen widespread, not only detrimental to the state, but also a violation of social rights and theeconomy at large, so that corruption needs to be categorized as crime eradication should bedone widely. various policies have been carried out by the government in tackling corruptionin the form of legislation and in various policies related to criminal law corruption. One ofthe criminal law policy in the field of corruption that is much discussed today is a moratoriumremission and parole. Based on the principles in the formation of legislation lex superiorderogat legi inferior, which means that the regulation of low position must not conflict withhigher regulations. moratorium remission and parole for inmates of corruption in Indonesiaissued by the Ministry of Law and Human Rights of the Republic of Indonesia, contrary toLaw No. 12 of 1995 concerning Corrections